Managing Revenue across Retail Channels: The Interplay of Service Performance and Direct Marketing. (September 2014) - Lund, Donald J.; Marinova, Detelina
Increased internal pressure to make marketing accountable, combined with market pressure from the proliferation of new service delivery channels, requires retailers to better understand the differential impacts of marketing efforts across channels now more than ever. In this article, the authors (1) develop and test a theoretically grounded framework for the interplay of objective service performance and direct marketing in shaping retail revenue over time through two distinct service delivery channels (on-site and remote) and (2) conceptualize service delivery channel–specific servicescapes as facilitative mechanisms for the effectiveness of objective service performance and direct marketing. The authors test the conceptual framework with multisource data from a major national pizza retailer comprising a field study based on a time series of 223 weeks across five stores of objective marketing and performance data (delivery time) and a cross-sectional survey of the retailer's customers. They find that objective service performance and direct marketing interact by exhibiting a trade-off effect contingent on specific aspects of the servicescape. When both objective service performance and direct marketing levels are high, servicescape quality design perceptions alleviate the trade-off effect in on-site delivery channels, and servicescape time/effort cost perceptions do so in remote delivery channels. The authors conclude with a discussion of implications for research and practice.